HUBUNGAN SOCIAL IDENTITY DAN SELF IDENTITY TERHADAP GREEN PURCHASE INTENTION PADA SISWA SMAS PGRI 1 KOTA BEKASI - Divania Fazrina (CV. ADIBA ASIHA AMIRA, 2025)
This study aims to determine the relationship between social identity and self identity on green purchase intention. The sampling technique used convenience sampling and the respondents in this study were 252 students of SMAS PGRI 1 Bekasi City. The measuring instruments used in this study are the social identity scale and the self identity scale. The results of this study indicate that the correlation coefficient between social identity and green purchase intention has a correlation coefficient of 0.169 with a significance of 0.007. And the relationship between self identity and green purchase intention shows a correlation coefficient of 0.170 with a significance value of 0.007, which is also significant at the 5% level. Furthermore, the relationship between social identity and self identity has a correlation coefficient of 0.182 with a significance value of 0.004. So it can be concluded that although the correlation is weak, there is a relationship between social identity and self identity on green purchase intention among students of SMAS PGRI 1 Bekasi City.